Multimodal cognitive and behavioral interventions for patients with MCI: a systematic review and meta-analysis on cognition and mood - Ying, Gelan; Perez-Lao, Ambar; Marsiske, Michael; Levy, Shellie-Anne; Smith, Glenn E. (Frontiers in Aging Neuroscience, 2024)
Background Research has increasingly suggested a benefit to combining multiple cognitive or behavioral strategies in a single treatment program for cognitively impaired older adults. Therefore, this systematic review and meta-analysis aimed to summarize results on the effects of multimodal cognitive and behavioral interventions versus control conditions on changes in cognition and mood in patients with mild cognitive impairment (pwMCI). Methods The review followed a general PRISMA guideline for systematic literature review with a format consisting of participants, interventions, comparators, and outcomes (PICO). Multilevel meta-analyses of aggregated efficacy were performed to assess the pooled effect sizes for cognitive and mood outcomes. Risk-of-bias, heterogeneity across studies, and publication bias were assessed for each outcome. Results After primary and reference searches, 18 studies with low or some concerns of risk of bias were included. Low heterogeneity was found for mood and cognition. Funnel plots did not indicate publication bias. All the studies assessed changes in cognition (n = 1,555) while seven studies with mood outcomes (n = 343) were included. Multilevel meta-analyses demonstrated moderate effect (Hedge’s g = 0.44, 95% CI = [0.21–0.67]) in cognitive outcomes and large effect in mood (g = 0.65, 95% CI = [0.37–0.93]). Subdomain analyses found low-moderate effects in global cognition, verbal and non-verbal memory, executive function, visuospatial abilities, and semantic fluency (0.20 < g < 0.50). Conclusion These findings showed comparable to larger effects of multimodal cognitive and behavioral interventions on cognition than pharmacological treatment. Future studies should focus on the longitudinal effects of multimodal interventions in delaying dementia. Systematic review registration: PROSEPRO, CRD42022349297.